(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Hemolytic anemia represents a heterogeneous group of disorders characterized by increased destruction of erythrocytes, leading to decreased red blood cell lifespan and impaired oxygen-carrying capacity. This article explores the major pathophysiological mechanisms underlying hemolysis, outlines the principal clinical variants, and provides a comprehensive review of modern diagnostic approaches, including laboratory, instrumental, molecular, and immunohematological methods. Hemolytic anemia is a complex hematologic condition in which erythrocytes undergo premature destruction due to intrinsic structural abnormalities or extrinsic damaging factors. The accelerated breakdown of red blood cells leads to reduced oxygen delivery, compensatory marrow hyperactivity, and systemic biochemical disturbances caused by released hemoglobin metabolites. This article provides an expanded scientific description of the biological cascade driving hemolysis, emphasizing how membrane defects, enzymatic insufficiencies, and immune-mediated mechanisms disrupt erythrocyte survival. Particular attention is given to the variation in clinical expression among hereditary and acquired forms, as well as the relevance of precise differentiation for patient outcomes. Modern diagnostic techniques—including cell morphology assessment, advanced biochemical profiling, immunohematologic testing, and genetic analysis—are thoroughly examined to demonstrate their essential role in establishing the etiology and severity of hemolytic processes.